ECO-BASED REASONED ACTION MODEL: THE ROLE OF MANAGEMENT CONTROL SYSTEM - Eka Ardhani Sisdyani (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2020)
This paper aims to enrich Fishbein and Azjen’s Theory of Reasoned Action  in predicting the emergence of green behavior by adding institutional-based control system to maintain green intention’s stability.  Intention’s stability is a crucial construct in realizing green behavior, though, it is affected by several instances such as: resources availability, individual capabilities, new information, and cooperation and commitment of individuals. For that reason, it is plausible to argue that the existence of institutional-based control directing green behavior, such as eco-based management control systems, namely levers of eco-control, can maintain and augment one’s intention to pursue green behavior. Thus, the paper contributes in enriching the knowledge of the emergence and persistence of green behavior in organizations.